Preparation of isotopically enriched 112, 116, 120, 124Sn targets at VECC. (July 2022) - Pandey, Ratnesh; Kundu, S.; Banerjee, K.; Bhattacharya, C.; Rana, T.K.; Mukherjee, G.; Manna, S.; Sahoo, J.K.; Pai, H.; Ghosh, T.K.; Roy, Pratap; Sen, A.; et al.
Abstract: Resistive heating and mechanical rolling methods have been employed to prepare isotopically enriched thin target foils of 116 Sn (∼380 μg/cm 2 ), 124 Sn (∼400 μg/cm 2 ) and thicker foils of 112 Sn (∼1.7 mg/cm 2 ), 120 Sn (∼1.6 mg/cm 2 ), respectively. Preparation of enriched targets with a small amount of material, selection of releasing agent for thin targets and separation of deposited material in solvent were among the several challenges during fabrication of the thin targets. The uniformity of the targets has been measured using 241 Am α-source. NaCl has been used as releasing agent in preparation of the thin targets. These targets have been successfully used in nuclear physics experiments at VECC. Highlights: Isotopically enriched targets of Sn from lowest to highest isotopes having different thicknesses have been prepared using vacuum evaporation and rolling techniques. NaCl has been used as releasing agent for preparation of thin target. Purity and surface study of these targets have been characterized by EDS and FESEM techniques. The measured energy values of elastically scattered 16 O have been compared with theoretical calculation LISE++.